Telaah Bibliometrik Tren Riset Creative Entrepreneurship dalam Bidang Pendidikan - Fahayu Priristia; Rizki Oktavianto; Reny Refitaningsih Peby Ria (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The dominance of vocational secondary education graduates as contributors to the open unemployment rate, as shown by the results of the BPS national labor force survey in 2023, provides a challenge faced by educational institutions to improve the distribution of graduates into the world of work. Optimizing creative entrepreneurship can be a solution to this problem. The implementation of various policies and practices related to creative entrepreneurship in the education sector is greatly helped by research. This study uses bibliometrics to identify and map various scientific publications to determine the topics, sources, authors, frequently referenced articles and main countries that discuss creative entrepreneurship in education. This research will also discuss the conceptual, intellectual, and social structure of the literature related to creative entrepreneurship. This bibliometric analysis used 258 Scopus-indexed journal articles published in the last ten years.. The discussion provides an overview of creative entrepreneurship research in education using tables, graphs, and mapping. It provides recommendations for future research related to creative entrepreneurship in education. The bibliometric review resulted in a conclusion that the prospect of creative entrepreneurship research in education is still relatively high. Further research is suggested on the topic of developing entrepreneurship learning based on leadership, problem-solving, creative thinking skills, and professional aspects.